Evaluation of the Marketing Influence on the Investment Attractiveness of the Company - Tyutyukina, Elena; Lukashenko, Inna; Sedash, Tatyana; Ivanushkina, Kristina; Danilov, Anatoly (Journal of Reviews on Global Economics, 2018)
The study considers marketing activities of companies and their influence on the companies' investment attractiveness. Based on the role and content of marketing in modern conditions, the authors evaluate investment attractiveness by indicators characterizing cash flows and efficiency of the company's activities. Two companies and set of criteria were selected to assess the impact of marketing on their investment attractiveness. Correlation analysis revealed the indicators which are influenced by marketing technologies most of all. Evaluation of the impact of the company's marketing activities on investment attractiveness showed certain methodological problems, which require further research.